Population parameters for traits defining trypanotolerance in an F2 cross of N'Dama and Boran cattle - Waaij, E.H. van der; Hanotte, Olivier H.; Arendonk, Johan A.M. van; Kemp, Stephen J.; Kennedy, D.; Gibson, John P.; Teale, A.J. (Elsevier, 2003)
Some West African Bos taurus cattle breeds such as the N'Dama and a number of West African Shorthorns are resistant to tsetse fly-transmitted trypanosomosis. The trait is termed trypanotolerance, for which changes in packed red cell volume percent (PCV) and growth rate following infection are generally considered to be indicators. An F22 population was created with the N'Dama and the Kenyan Boran (a trypanosusceptible breed). Two hundred and fourteen F2N'Dama x Boran cattle were infected by the bites of tsetse flies infected with the cloned parasite Trypanosoma congolense IL1180. Body weight, PCV, and parasite counts were recorded on a weekly basis for 150 days post infection. Seventeen derived traits were defined based on the data recorded; seven derived from bodyweight, seven from PCV, two from parasite counts recordings and survival. Average values among the F2 animals were intermediate between those of N'Dama and Boran control animals for all traits. The highest and lowest responders in the F2 group, when selected on maximum decrease in PCV or on maximum decrease in body weight, were equal to the averages of the Boran and N'Dama animals, respectively. The most trypanotolerant F2 animals followed similar courses to N'Dama controls and the most susceptible animals followed similar courses to the Borans. There were moderate to low phenotypic correlations (0.00-0.32) between average log(parasite count) or number of times an animal was detected parasitaemic, and the PCV and body weight derived traits. There were low to moderate phenotypic correlations (0.02-0.74) between and within (0.01-0.96) PCV and body weight derived traits. Most of the traits defined in this study were heritable. Heritabilities ranged from 0.01 for PCV recovery, to 0.88, for initial PCV. Some F2 animals seemed to be able to control anaemia and have a higher average body weight and body weight gain than the pure-bred N'Dama. Overall, in this study body weight change following infection seems an appropriate and easy to measure indicator of trypanotolerance.